O entre do carvão ao corpo - em - arte de ator-brincante - Monteiro Júnior, Alan Carlos (2011)
I propose with this paper a reflection on the experiences contained in the creation of the body- in-art (FERRACINI, 2006a, b) that originated the show Rosmaninhos... This process was developed within the coletivo UZUME teatro from João Pessoa PB, through recreations and resignifications of the corporeity and physicality contained in the steps, loas, aboios, songs and choreography observed in the manners that Mestre Zequinha plays in his group of Cavalo Marinho (Sea Horse), resident in the city of Bayeux - PB, and starting from the appropriation of the text Hamlet of William Shakespeare. The body-in-art is understood in this work as a vectorial body that dilates its daily functionality, recognizing a potential learning area capable to generate creative escape lines that destabilize the "subject centered in an individuality and identity" (FOUCAULT apud FERRACINI, 2006b, p.14), being open to the differentiation of itself, indicating the possible existence of an itself-other and of the exchange-in-art space. This process of construction of the body-in-art based on Master Zequinha s ways of playing the Cavalo Marinho was methodically guided by the appropriation of the coletivo UZUME teatro of the stages of Observation, Codification and Theatricalization contained in the technique of corporal mimeses proposed by the LUME Teatro (Campinas - SP). That use resulted in two phases: Active Observation and Composition of the body-in-art. Through the repetition of these aesthetic matrixes of the Cavalo Marinho, the actors discovered actions that when, codified and organized, can configure their body-in-art, which created a vectorial exchange-in-art space to what was found in the Cavalo Marinho party. This search proposed the means of potentiating the actors' work when it comes to a preparation that allowed to dilate the scenic presence and stimulated the production of actions, which culminated in the mounting of the show Rosmaninhos...